Special Issue of Selected Contributions from the Seventh Swedish Language Technology Conference (SLTC 2018) - Hercules Dalianis; Robert Östling; Rebecka Weegar; Mats Wirén (Northern European Journal of Language Technology)
This Special Issue contains three papers that are extended versions of abstracts presented at the Seventh Swedish Language Technology Conference (SLTC 2018), held at Stockholm University 8-9 November 2018.1 SLTC 2018 received 34 submissions, of which 31 were accepted for presentation. The number of registered participants was 113, including both attendees at SLTC 2018 and two co-located workshops that took place on 7 November. 32 participants were internationally affiliated, of which 14 were from outside the Nordic countries. Overall participation was thus on a par with previous editions of SLTC, but international participation was higher.